A qualidade das águas subterrâneas no município de Fortaleza - CE - LEMOS, Ediu Carlos Lopes (2019)
study aimed to evaluate the quality of groundwater in the city of Fortaleza, capital of Ceará, Northeast Brazil, with 313.8 km2 with a total of 2,416,920 inhabitants with a density of 6,855 inhabitants. Access to town is via the main roads that comprise the municipality other state or interstate regions, they being BR 116 (south), BR 222 (west) and the CE 020 (east). The stages of work consisted of a literature review and documentary compilation of registration data from 99 wells and 99 sheets of physico-chemical properties were generated location maps, hydrogeological maps and points of isovalue pH, TDS, C.E, chlorides and nitrate, the data of physical-chemical analysis were plotted on Piper diagram for classification ionic diagram Schöller & Berkaloff to check the potability of groundwater and the U.S. Salinity Laboratory diagram to evaluate the use in irrigation. The average temperature in Fortaleza is located in the range of 28°C to 26ºC, being higher in the months of November and December. Geologically the county is characterized by ocorrence of Cenozoic sediments and Precambrian rocks. Geomorphologically, the city is basically constituted by the Coastal Plain and Pre-Littoral Glacis. The vegetation units of the study area are characterized in pioneer vegetation, kills the rear of dunes, coastal tableland vegetation, swamp vegetation, riparian vegetation, aquatic vegetation, manmade vegetation. The climatic variables and water balance of the area, define two very different periods, a rainy season that runs from February to May and a block of drought that stretches from August to December. In Fortaleza are found two (2) aquifers: the sedimentary (made up of Dunes/Paleodunes, Barreiras, Alluvial), and the Middle Cristalline, these two units differ widely as to the vocation aquifer to store and transmit water. On the chemical characteristics of water of 99 wells tested, the electrical conductivity showed overall average of 623 μS/cm at 25 ° C, where 8% of samples had values greater than 1,000 μS/cm, reaching a maximum of 2050 μS/cm, while for TDS 76% of samples were classified as low to medium salinity, 24% had values exceeding 500 mg TDS/L, being classified as medium to high water salinity. With respect to the hardness of water 50% have features of "hard" to "very hard", 18% feature little stiff and 32% are classified as type "soft", all had values within the limit established by Ordinance nº518 Ministry of Health up to 500 mg/L CaCO3. the groundwaters in the area are nitrate, whereas, 25.5% of samples showed values higher than recommended for N-NO3, surpassing by up to 460%, the maximum recommended by the Ministry of Health. According to the Piper diagram, groundwater was classified chlorinated sodium, sodium bicarbonate followed by water. There is a predominance for the waters of this region, according to the relationship between ion anions and cations, Cl- > HCO3 - > SO4 2- and Na+ > Mg2+ > Ca2+. The diagram Schöller & Berkaloff shows that the groundwater of the area have acceptable levels of drinking. According to the classification of the U.S. Salinity Laboratory diagram, the groundwater of the study area are located mainly in S3 and S4 class that denotes a high risk of sodium, and the C2 and C3 denote a medium to high risk of salinity (52% in classes C2–S3 and C2 – S4), presenting certain restrictions on use for irrigation, industrial use, most of these waters are off limits, with ledge for pH, hardness, TDS, magnesium, nitrate and chloride, well above the benchmarks in more than 85% of the tests.